Avaliação no ensino de línguas estrangeiras: análise bibliométrica de artigos publicados em periódicos nacionais (1985 a 2018) - Borja, Bruno Chaves (2020)
Classroom assessments are a key part not only of foreign language teaching, but of all teaching and learning scenarios. They are given so much weight that sometimes other equally important stages in the learner’s education process do not receive enough attention. The importance of assessment is justified because it is an intrinsic part of the teaching and learning processes. Assessment provides the teacher with a wealth of information to be used in future classroom practices, in the planning of courses and also in the management of students and learning tasks (REA-DICKINS; GERMAINE, 1993). Thus, this research investigates, through documental and bibliometric analysis, the scientific production on assessment in the area of foreign language teaching published in Brazilian journals between 1985 and 2018. Sucupira platform of Capes is used to search for articles published in A1 (High Scored) journals (Quadriennium 2013-2016), in order to identify, bibliographically and bibliometrically, the number of publications that deal with the topic assessment in foreign language teaching and its main contributions to the topic. In other words, this study seeks to identify and discuss to what extent the publications contribute to a new look on evaluation in foreign language teaching. The results show a lack of current national research in the journals analyzed, as well as frequent interest for proficiency tests.